THE INFLUENCE OF FINANCIAL LITERACY, PERCEIVED EASE OF USE, PERCEIVED RISK, AND LIFESTYLE MODERATED BY GENDER ON THE ADOPTION OF QRIS AS A CASHLESS PAYMENT METHOD (A Case Study of Generation Z in Greater Bandung) - Fella Fitriani; Abdul Mukti Soma (PT. Jurnal Center Indonesia Publisher, 2026)
The growth of internet users in Indonesia has increased significantly from last year and penetration has reached 79.5% by the beginning of 2024. Reaching 13.66% of the Indonesian population has made payments.e-commerceregularly cashless with e-wallet or digital wallet. This reflects that Indonesian society is undergoing transformation by implementing digital wallet programs.cashless society or change of cash payment to non-cash. The use of QRIS is one of the instruments that support the BI program in creating cashless society. The existence of digital transformation is only supported by 6.84% of the Indonesian population who are digitally literate, which means that more than 90% of the people in Indonesia are not digitally literate in facing this digital transformation. The aim of the research is to determine the influence of digital transformation.financial literacy, perceived ease of use, perceived risk, And lifestyle moderated by the rolegender towards the adoption of the use of QRIS ascashless payment on Generation Z in Bandung Raya. The theory from this study uses Technology Acceptance Model 1 because the theory is relevant to the objectives of this research. The model focuses on the main factors affecting technology acceptance, one of which isperceived ease of usewhich is modified within the research framework. The research method used is quantitative with the aimcausal descriptive which is applied by usingTechnology Acceptance Model (TAM). The time for implementing the study iscross sectionaland the research backgroundnon-contrived. The analysis tool usesStructural Equation Model (SEM) basedPartial Least Square (PLS) to test the tentative hypothesis proposed to 30 Generation Z QRIS users in Greater Bandung. During the sampling process, 113 respondents were recruited. The preliminary findings indicate that all independent variables are valid, as all questionnaire items have r-values > 0.361 at a significance level of 0.05. The results of this study show that eachfinancial literacy, perceived ease of use, perceived risk, And lifestyle has a significant positive effect onbehavior intention on Generation Z in Bandung.Gender is known to moderate the influence of each independent variable in this study onbehavior intention on Generation Z in Greater Bandung. Academic suggestions from this study are intended to enable future research to explore the indicators of each independent variable in more depth and expand the sample size. Practical suggestions for service providerse-wallet to focus on reducing risks and increasing personal security and develop strategies to build user trust inlifestyle owned by the user.